PERSEPSI MASYARAKAT TERHADAP WISATA HALAL DI KABUPATEN PRINGSEWU - Rosita, Pratiwi Dian; Anwari, Addini Alifa; Rahmahwaty (Jurnal Ekonomi Syariah dan Pariwisata Halal, 2023)
This research aims to test the Theory of Planned Behavior (TPB) regarding the influence of concept perceptions on attitudes, perceptions of development on attitudes in the Pringsewu community regarding halal tourism. This research design was descriptive and correlational involving 300 respondents from the Pringsewu area. collect data through surveys by filling out questionnaires. The influence of concept perceptions on the attitudes of the Pringsewu community regarding halal tourism. This research shows that there is an influence between perceptions on people's attitudes regarding halal tourism. The public's perception of halal tourism lies in its facilities. The facility criteria are included in one of the GMTI (Global Muslim Travel Index) criteria. The government is expected to prioritize the development of halal tourism facilities.